1976
DOI: 10.1021/jm00228a021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1- and 2-substituted indazoles as anthelmintic agents

Abstract: Selective synthesis of 1- and 2-acyl-, alkoxycarbonyl-, and carbamoylindazoles are described. Spectroscopic data which were the basis for structural assignments are presented. These compounds, particularly methyl 2H-indazole-2-carboxylate and N-heptyl-N-methyl-2H-indazole-2-carboxamide, lack the spectrum of anthelmintic activity of the benzimidazole and benzotriazole anthelmintics to which they are structurally related.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The reaction of indazole 1 with ClCO 2 Me in the presence of Kt-BuO, at room temperature, gave only the N-1 isomer 2a in excellent yield (99%). The synthesis of 2a was previously reported by Kingsbury et al [19], who showed that the reaction of ClCO 2 Me with indazole 1 in the presence of an amine, such as pyridine or triethylamine, gave the N-1 isomer 2a (57%) at room temperature and the N-2 isomer at -78 ºC. The synthesis of 2b, 2c, 3b and 3c, using also a nucleophilic displacement reactions with bromo esters, was first reported by Auwers in 1926 [20], but no spectroscopic characterisation has been described.…”
Section: Synthesismentioning
confidence: 99%
“…The reaction of indazole 1 with ClCO 2 Me in the presence of Kt-BuO, at room temperature, gave only the N-1 isomer 2a in excellent yield (99%). The synthesis of 2a was previously reported by Kingsbury et al [19], who showed that the reaction of ClCO 2 Me with indazole 1 in the presence of an amine, such as pyridine or triethylamine, gave the N-1 isomer 2a (57%) at room temperature and the N-2 isomer at -78 ºC. The synthesis of 2b, 2c, 3b and 3c, using also a nucleophilic displacement reactions with bromo esters, was first reported by Auwers in 1926 [20], but no spectroscopic characterisation has been described.…”
Section: Synthesismentioning
confidence: 99%
“…Extensive literature survey revealed that a huge number of methods have been reported for the synthesis of substituted 1H-indazoles. One general route involves diazotization of o-alkylsubstituted anilines followed by acid promoted cyclization [18,19], functionalized sydnone, oxadiazole condensation/Boulton-Katritzky rearrangement [20], intramolecular dehydration from common arylamino oximes/ o-aminobenzoximes [21,22], condensation of arynes with nitrile imines/ diazomethane derivatives/diazo compounds/hydrazones [23,24], condensation of hydrazine to o-halo/o-alkoxy arylhydrazone [25,26]. In addition to the above methods, other intra molecular cyclizations are also reported for the synthesis of indazole derivatives, for example Pd-mediated ring closure of hydrazine and hydrazone based derivatives [27,28], copper catalyzed intramolecular amination of o-haloarylcarbonyl compounds/2-halobenzohydrazides [29,30], CuI promoted cyclization of an aryl hydrazone under microwave irradiation [31], FeBr 3 /O 2 -mediated intramolecular C-H amination of arylhydrazones [32], PIFA-mediated oxidative cyclization of o-amidobenzanilides [33], Rhodium-catalyzed cyclocarbonylation of azobenzenes [34], Zinc catalyzed reductive cyclization of o-nitrobenzanilides [35], layered Zirconium sulfophenyl phosphonate catalyzed synthesis from condensation of 1,3-diones and hydrazines under solvent free conditions [36] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…
A two-stage synthesis of 2H-indazoles has been established, based on consecutive reactions of reduction of 2-alkyl-, 2-cyclopropyl-, and 2-arylcarbonylazobenzenes to phenylazo-substituted benzyl alcohols and intramolecular heterocyclization of the reduction products under the influence of organic acids.In recent years there has been a considerably strengthened interest in the synthesis and study of the medicobiological properties of derivatives of 2H-indazoles, resulting from the observation in a series of compounds which are seldom encountered in nature, a class of heterocycles with a wide range of biological activity: antiangiogenic [1], anticarcinogenic and anti-inflammatory [2,3], antimicrobial [4], antifungal [5,6], cytotoxic [7], and antihelminthic [8]. In addition compounds of this class show potential as inhibitors of NO-synthetases [9, 10], protein kinases [11,12], tubulin [13], modulators of X-receptors of the liver [14], and they also show properties of male contraceptives [15,16].

The discovery of the biological activity of the 2H-indazoles caused the real problem of the synthesis of new derivatives of this class of heterocycles.

…”
mentioning
confidence: 99%
“…In recent years there has been a considerably strengthened interest in the synthesis and study of the medicobiological properties of derivatives of 2H-indazoles, resulting from the observation in a series of compounds which are seldom encountered in nature, a class of heterocycles with a wide range of biological activity: antiangiogenic [1], anticarcinogenic and anti-inflammatory [2,3], antimicrobial [4], antifungal [5,6], cytotoxic [7], and antihelminthic [8]. In addition compounds of this class show potential as inhibitors of NO-synthetases [9, 10], protein kinases [11,12], tubulin [13], modulators of X-receptors of the liver [14], and they also show properties of male contraceptives [15,16].…”
mentioning
confidence: 99%